Using Large Language Models in Software Requirements Analysis - Son, Han Seong (Edelweiss Applied Science and Technology, 2025)
Improperly specified requirements can cause hazardous situations when they are designed and implemented into software. For example, missing requirements may lead to deaths and injuries. Software requirements analysis, which involves identifying and correcting inadequately defined requirements, plays a crucial role in reducing the possibility of hazardous situations caused by safety-critical software. This work proposes a requirements analysis method for detecting missing requirements and minimizing sets of requirements. The proposed method utilizes an LLM and a prompt pattern. The feasibility and effectiveness of the proposed method have been demonstrated by applying it to the existing requirements.